Controlling DC microgrids in communities, buildings and data centers. Issue 3 (15th May 2020) - Kolluri, Ramachandra Rao; Mareels, Iven; de Hoog, Julian
Abstract : Microgrid technology is poised to transform the electricity industry. In the context of commercial/domestic buildings and data centers, where most loads are native direct current, DC microgrids are in fact a natural choice. Voltage stability and current/power‐sharing between sources within a DC microgrid have been studied extensively in recent years. DC voltage droop control is known to have its drawbacks in that current or power‐sharing is relatively poor. To eliminate this drawback, some have proposed to add a communication‐based consensus control in addition to the primary voltage droop control loop. The current sharing performance is improved, however, the voltage deviation inherent in droop control requires a further, slower control to achieve voltage quality control. To overcome this complication, and reduction in response time, a low latency communication‐based control technique that achieves proportional current sharing without significant voltage deviations is proposed in this work. The stability of the proposed control technique is compared to state‐of‐the‐art using eigenvalue and transient analyses. The negative impact of communication delays on proposed control is discussed in detail.